Nichifor Crainic and the Christian-Nationalism from the Romanian Space - Morariu, Iuliu-Marius (Forum Theologicum Sardicense, 2025)
Using information from Nikifor Crainic's publications in peri- data, this article aims to pre- resent how the Christian nationalism of this Romanian author is reflected in his journalistic works and to identify the main elements of his thought. It explores aspects such as ethnocracy, messianism, suffering, and national evolution. Additionally, the article examines how prominent nationalist movements of the time with which Crainic was engaged, such as Nazism and Fascism, influenced his ideas and affected his originality.